The Hepatitis B Virus Interactome: A Comprehensive Overview - Van Damme, Ellen; Vanhove, Jolien; Severyn, Bryan; Verschueren, Lore; Pauwels, Frederik (Frontiers in Microbiology, 2021)
Despite the availability of a prophylactic vaccine, chronic hepatitis B (CHB) caused by the hepatitis B virus (HBV) is a major health problem affecting an estimated 292 million people globally. Current therapeutic goals are to achieve functional cure characterized by HBsAg seroclearance and the absence of HBV-DNA after treatment cessation. However, at present, functional cure is thought to be complicated due to the presence of covalently closed circular DNA (cccDNA) and integrated HBV-DNA. Even if the episomal cccDNA is silenced or eliminated, it remains unclear how important the high level of HBsAg that is expressed from integrated HBV DNA is for the pathology. To identify therapies that could bring about high rates of functional cure, in-depth knowledge of the virus’ biology is imperative to pinpoint mechanisms for novel therapeutic targets. The viral proteins and the episomal cccDNA are considered integral for the control and maintenance of the HBV life cycle and through direct interaction with the host proteome they help create the most optimal environment for the virus whilst avoiding immune detection. New HBV-host protein interactions are continuously being identified. Unfortunately, a compendium of the most recent information is lacking and an interactome is unavailable. This paper provides a comprehensive review of the virus-host relationship from viral entry to release, as well as an interactome of cccDNA and HBx.